The crystal structure of 4-chloro-2-(quinolin-8-yl)isoindoline-1,3-dione, C17H9ClN2O2 - Yang Fan; Yao Lin; Zeng Xu-Li (Zeitschrift für Kristallographie - New Crystal Structures)
C17H9ClN2O2, monoclinic, P21/c (no. 14), a = 13.6888(4) Å, b = 8.3775(2) Å, c = 12.9180(3) Å, β = 110.515(3)°, V = 1387.46(7) Å3, Z = 4, R gt(F) = 0.0420, wR ref (F 2) = 0.1224, T = 293(2) K.